The childbirth experience: obstetric and psychological predictors in Italian primiparous women - Valentina Fenaroli; Sara Molgora; Serena Dodaro; Alessandro Svelato; Livia Gesi; Giulia Molidoro; Emanuela Saita; Antonio Ragusa (BMC, 2019)
Abstract Background The experience of childbirth crucially impacts a mother's psychological well-being and the mother-infant relationship. It is recognised that negative births can be linked to different forms of discomfort, both for the mother as well as for the infant. This prospective longitudinal study aimed to study the effect of obstetric and psychological variables on women's subjective experience of childbirth. Methods 111 primiparous Italian women completed a set of questionnaires at 38-40 weeks of pregnancy (Time 1) and 1-5 days after childbirth (Time 2). Sociodemographic and obstetric information were collected. Data about the childbirth were obtained from the mother's ward birth records. Women completed the Wijma Delivery Expectancy/Experience Questionnaire both before and after childbirth. Results The subjective experience of birth was significantly predicted by the duration of the expulsive phase (β = .26; p < .05), the use of epidural analgesia (β = .21;  p< .05) and by fear of birth (β = .21; p < .05). The effect of mode of birth and duration of the dilatation phase on women's birth experience was not found. Conclusions In our study, neither instrumental childbirth nor caesarean section have a significant effect on women's birth experience. Instead, both a longer expulsion phase and epidural analgesia contribute to the negative experience. Moreover, the higher the fear of birth, the worse the women's emotional experience. These findings confirmed the role of obstetric and psychological variables on birth experience. More investigation about this topic could be useful to develop specific interventions to prepare women for birth.